Analisis Penerapan Target costing Dalam Upaya Efisiensi Biaya Produksi Pada PT. Inko Networks Indonesia - Zulfa, Arliyana Revika; Norsita, Mega (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
Companies have difficulty in making production costs efficient, one of the reasons companies find it difficult to steamline production cots is that they still use simple calculation methods. The purpose of this research was to determine the impact of implementing target costing in efforts to efficiency production costs at PT. Inko Networks Indonesia. The type of research used in this research is descriptive qualitative approach in the form of a case study. The data obtained in this research in based on primary data in the form of interviews, observations and documentation studies, as well as secondary data in the form of sales data, production data, financial reports and other supporting data. The result of this research show that implementing target costing is a good alternative effort in an effort to streamline the companies production costs and can influence the increase in profit obtained by the company by carring out value engineering againts excessive costs. Based on the result of the analysis, the target costing calculation shows that there is a production costs efficiency of 3.6% with the total production costs incurred by the company before implementing target costing were IDR2,422,372.56/ton, whereas after implementing target costing it was IDR2,336,239.95/ton and there was an increase in profit obtained by the company by 12%.